Estrutura da comunidade de morcegos (Mammalia, Chiroptera) em remanescentes florestais urbanos, Palotina, Paraná - Ribeiro, Edmaykon Rafael Gaias (2022)
Bats belong to the second largest order within mammals, being one of the groups with the highest abundance in Brazil. However, the process of fragmentation of natural environments associated with people's common sense is leading to a process of conditioning bat species to anthropized environments, including urban forest remnants.The objective of this work was to inventory the assembly of bats in urban forest remnants in the municipality of Palotina-PR, evaluate how bats are distributed spatially in the environment, correlating ecological indices, verifying the main families and their eating habits. The samples were collected monthly in three urban fragments of Semidecidual Seasonal Forest, located in Palotina, western Paraná State, between December 2020 and November 2021. Forest fragments have distinct sizes, location and vegetation. Nine mist nets arranged approximately 2.5 m from the ground for three nights for four hours were used. The captured individuals were placed in cotton bags and taken to the field base. After a period of one hour of capture time, the individuals were screened, identifying the species. The individuals were marked with numbered washers and released at the place where they were collected. Ecological metrics were used to evaluate indices, as well as the accumulation curve was made to verify if there were differences. For these analyses, the packages used were iNEXT and ggplot2.To compare eating habits between the fragments, tests were performed to compare means, nonparametric ANOVA in both cases. A total of 199 captures were obtained, distributed in four families (Phyllostomidae, vespertilionidae, noctilionidae and molossidae), and fifteen species. In general, species of four distinct eating habits (friivores, insectivores, omnivores and piscivores) were collected.Insectivorous (6 species) and friivore species occurred at all points, being friivores with higher abundance (7 species). Phyllostomus hastatus, an omnivorous species, was restricted to the most conserved fragment, as was Carollia perspicillata (frugivore). The piscivore species, Noctilio leporinus (Linnaeus, 1758), was restricted to point two.Sample point three had higher species richness, with 13 records. The present study allowed the registration of four new species for the municipality of Palotina. The statistical data did not show differences between the environments. The trophic guild (frugivores) were more representative. The data obtained provide a better understanding of the biology of some species in regions of the state little studied.